R. C. van Caengem. Judges, Legislators and Professors. Chapters in European Legal History, 1987 - Czarnota, Adam (Czasopismo Prawno-Historyczne, 1989)
Recenzja: R. C. van C a e n g e m, Judges, Legislators and Processors. Chapters in European Legal History, Cambridge University Press, Cambridge 1987